Measurement of soft-drop jet observables in pp collisions with the ATLAS detector at √s=13 TeV - Aad, Georges; Anders, Christoph; Andrei, George Victor; Bolz, Arthur; Dunford, Monica; Ferreira de Lima, Danilo Enoque; Franchino, Silvia; Helary, Louis; Henkelmann, Lars; Jongmanns, Jan; Klassen, Martin; Krishnan, Anjali; et al. (Physical review, 2020)
Jet substructure quantities are measured using jets groomed with the soft-drop grooming procedure in dijet events from 32.9 fb(-1) of pp collisions collected with the ATLAS detector at root s = 13 TeV. These observables are sensitive to a wide range of QCD phenomena. Some observables, such as the jet mass and opening angle between the two subjets which pass the soft-drop condition, can be described by a high-order (resummed) series in the strong coupling constant alpha(s). Other observables, such as the momentum sharing between the two subjets, are nearly independent of alpha(s). These observables can be constructed using all interacting particles or using only charged particles reconstructed in the inner tracking detectors. Track-based versions of these observables are not collinear safe, but are measured more precisely, and universal nonperturbative functions can absorb the collinear singularities. The unfolded data are directly compared with QCD calculations and hadron-level Monte Carlo simulations. The measurements are performed in different pseudorapidity regions, which are then used to extract quark and gluon jet shapes using the predicted quark and gluon fractions in each region. All of the parton shower and analytical calculations provide an excellent description of the data in most regions of phase space.
Das "s" steht im Titel unter dem Wurzelzeichen
Gesehen am 25.06.2020
ATLAS Collaboration: G. Aad, C.F. Anders, V. Andrei, A.E. Bolz, M. Dunford, D.E. Ferreira de Lima, S. Franchino, L. Helary, L. Henkelmann, J. Jongmanns, M. Klassen, A. Krishnan, A. Kugel, H. Meyer zu Theenhausen, T. Mkrtchyan, F. Napolitano, P.S. Ott, M. Sahinsoy, A. Schoening, H.-C. Schultz-Coulon, T.M. Spieker, R. Stamen, P. Starovoitov, S. Suchek, L. Vigani, J. Wang, S.M. Weber, M. Wessels, X. Yue und 2924 weitere